A Rare Adnexal Tumor of Head & Neck: Eccrine Spiradenoma - Syauqina Syasya, Binti Mohd Yusoff; Marliza, H; Ng, Boon Han Kevin (ClinMed International Library, 2021)
Introduction: Eccrine Spiradenoma is a rare connective tissue tumor arising from the dermis of well differentiated eccrine sweat gland. It is considered benign nature, nonetheless, reported malignant cases are extremely rare. The most common presentation symptom is localized intradermal swelling and complete surgical excision is the gold standard in managing these cases. Aim: This case report is undertaken to document a rare case of adnexal tumor of head and neck as well as sharing our experience to peer medical practitioners. Case study: We present a case of a 68-year-old lady, presented to a tertiary medical centre with a localized nodular right posterior neck swelling for the past 10 years, which underwent complete excision. Results and discussion: Following complete surgical excision and thorough surveillance, there is no evidence of recurrence and malignant transformation. Conclusions: Eccrine Spiradenoma is an extremly rare adnexal tumor that could involve head and neck, with reported cases of recurrence and malignant transformation that need to be closely observed and intervened should it present.